Retóricas em disputa: o debate intelectual sobre as políticas de ação afirmativa para estudantes negros no Brasil - Karine Pereira Goss (Ciências Sociais Unisinos)
The implementation of affirmative action politics for black students in the Brazilian public universities has generated an intense debate in several social spheres. The discussions on the affi rmative action politics have not only mobilized organized actors of the Brazilian civil society as well as the national intelligentsia. In parallel to the debate installed in the media from 2002, an academic dispute around the subject was also initiated. To understand the reason of the dispute between the Brazilian intellectuals on the necessity or not of these politics application constitute the main objective of the research. For this, the main proposals presented for social scientists, more specifi cally anthropology and sociology representatives will be analyzed. It has at least two well demarcated positions in social sciences regarding the subject: intellectuals contrary to the affirmative action politics and those favorable of. Their arguments will be analyzed from a typology created for Albert Hirschman (1992). The authors who develop arguments in opposition to the affirmative actions are partisan of a called rhetoric of conservative, while the ones that defend such politics are classified as partisan of a progressive rhetoric. Hirschman delimits three thesis of the rhetorical conservative that have been elaborated by intellectuals, many of them social scientists, at different times, evaluating politics as progressive and/or reformist: the thesis of perversity, the thesis of futility and the thesis of threat. For each thesis of the rhetorical conservative, the author elaborates progressive counterparts, originating pairs that oppose and complement each other. It is possible to conclude that the two rhetorics in shock reflect differentiated positions of intellectuals in relation to science and politics. Moreover, the partisans of the two rhetorics share diverse conceptions regarding important concepts used in Brazilian social sciences, "race" and of "mestization". As much as the entailing of the intellectuals to science and the theoretical matrices they use to explain the nation lies on their relative different positioning to the affi rmative action implementation for black students in Brazil.